Ziprasidone augmentation for anxious depression. (November 2016) - Ionescu, Dawn F.; Shelton, Richard C.; Baer, Lee; Meade, Kathryn H.; Swee, Michaela B.; Fava, Maurizio; Papakostas, George I.
Abstract : Previously, we found an anxiolytic effect of ziprasidone augmentation to escitalopram (compared with placebo augmentation) in patients with depression in an 8-week, randomized, double-blind, parallel-group, placebo-controlled trial. Here, we carried out a post-hoc analysis, comparing changes in the Hamilton Depression and Anxiety Rating Scales between patients with anxious depression versus nonanxious depression, using a moderator analysis. Hamilton Depression Rating Scales total change scores from baseline and endpoint were not significantly different (interaction term P =0.91) in patients with anxious depression on ziprasidone augmentation ( n =19; −9.1±4.9) or placebo ( n =19; −6.1±8.9) versus patients without anxious depression on ziprasidone ( n =52; −5.5±6.7) or placebo ( n =49; −2.3±4.5). There was a trend toward statistical significance (interaction term P =0.1) in favor of patients without anxious depression for a difference in Hamilton Anxiety Rating Scale total change scores from baseline to endpoint [patients with anxious depression on ziprasidone augmentation ( n =19; −2.7±5.3) or placebo ( n =19; −3.3±5.8) versus patients without anxious depression on ziprasidone ( n =51; −3.9±6.6) or placebo ( n =44; −0.9±4.7)]. Ziprasidone augmentation was equally efficacious in treating depression in patients with versus without anxious depression. However, the observed anxiolytic effect for patients with higher anxiety was not clinically significant.